Prosthetic Joint Infection from Carbapenemase-Resistant Klebsiella pneumoniae Successfully Treated with Ceftazidime-Avibactam - A. Schimmenti; E. Brunetti; E. Seminari; B. Mariani; P. Cambieri; P. Orsolini (Case Reports in Infectious Diseases)
Antimicrobial resistance in Gram-negative bacteria, particularly Enterobacteriaceae, has become a leading cause of morbidity and mortality and a serious public health concern. Gram-negative bacteria carrying extended-spectrum beta-lactamase (ESBL) enzymes now represent a significant proportion of all bacteria isolated from different countries worldwide. Furthermore, the increasing number of isolates carrying carbapenemases in recent years includes multidrug-resistant (MDR), extensively drug-resistant (XDR), and pandrug-resistant (PDR) bacteria. Here, we describe what, to our knowledge, is the first case of a patient with a prosthetic joint infection from carbapenemase-resistant Klebsiella pneumoniae (CRKP) successfully treated with ceftazidime-avibactam in Italy.